Exploring How TOEFL Preparation Classes Support English Development of Non-English Majors across Various Study Programs - Tira Nur Fitria (Epigram, 2026)
This study describes the role of TOEFL preparation classes in supporting the English language development of non-English major students across different study programs in the Institute of Technology Business AAS Indonesia, focusing on vocabulary, listening, reading, and structure and grammar skills. This study employs a descriptive qualitative research design. The finding shows that TOEFL preparation classes play an important role in improving the English proficiency of non-English major students who often have limited exposure to academic English and may face challenges in vocabulary, listening, reading, and grammar skills required in standardized tests. Through systematic instruction, guided practice, and strategic learning approaches, these classes help students strengthen their language abilities while preparing them for the TOEFL test. Vocabulary instruction emphasizes understanding word meanings in context through activities such as learning high-frequency academic words, identifying synonyms and antonyms, analyzing word families and collocations, and applying context clues and test-taking strategies. Listening instruction focuses on helping students comprehend spoken English in academic situations by exposing them to different accents, authentic materials, and technologies such as Text-to-Speech, while also training them to use strategies like note-taking and identifying main ideas. In reading instruction, students develop the ability to understand academic texts by learning text structures, recognizing key vocabulary, and applying strategies such as skimming, scanning, and identifying topic sentences. The Grammar section strengthens students’ understanding of English sentence patterns through topics such as subject–verb agreement, verb tenses, clauses, modifiers, and parallel structure, along with practice in Structure and Written Expression questions and strategies for identifying subjects, verbs, and common grammatical errors. Through continuous practice and structured instruction, students gradually improve their comprehension, grammatical accuracy, analytical skills, and confidence in answering TOEFL questions.